Physical and mathematical modeling of ignition, combustion and detonation of silane-hydrogen-air mixtures. (September 2017) - Tropin, D.A.; Fedorov, A.V.
Abstract: Studies of ignition limits, combustion and detonation of silane are now actual due to fire safety of industrial plants using silane. In particular, the silane is widely used in semiconductor industry as a source of silicon, which is obtained by combustion of silane. In this paper, the development of physical and mathematical model of ignition, combustion and detonation of the mixture of silane, hydrogen, oxygen and an inert gas (nitrogen, argon) is proposed, based on detailed kinetics. The comparison with experimental data on the ignition delay time of silane, hydrogen, oxygen and nitrogen mixture versus temperature behind the reflected shock wave through the three criteria of ignition of the mixture showed that the model with detailed chemical kinetics satisfactorily describe the experimental data. Furthermore, the ignition limits (upper and lower) of the mixture of silane - oxygen and silane - air at pressures from 0.05 to 1.1 atm and temperatures between 350 and 640 K on the basis of detailed chemical kinetics model were found. The effect of the silane - air mixture composition on the ignition limits was found. It was shown that the increasing of silane amount in mixture change the critical temperature of ignition non-monotonically. Highlights: It was proposed the model of ignition and combustion of silane/hydrogen/oxygen/nitrogen mixture, based on detailed kinetics. It was shown that the model satisfactorily describe the experimentally observed ignition delay times of the mixtures. It were found the ignition limits of the silane/oxygen and silane/air mixtures. It was found the effect of the silane/air mixture composition on the ignition limits. It was shown that the increasing of silane amount in mixture change the critical temperature of ignition non-monotonically.